Complex of Thermoelectric Equipment for Diagnostics and Treatment of Ophthalmological Diseases - Kobylianskyi, R.R.; Lysko, V.V.; Zadorozhnyy, O.S.; Pasechnikova, N.V. (Journal of Thermoelectricity, 2025)
The article presents the prospects for the use of new models of thermoelectric equipment developed to solve some urgent problems of ophthalmology, in particular the justification and implementation of the technology of controlled local artificial hypothermia of the eye in vitreoretinal surgery. Thermoelectric devices for measuring intraocular temperature, epibulbar temperature, and heat flux on the surface of the eye were demonstrated, which allow for comprehensive perioperative monitoring of thermal processes in the eye during vitreoretinal surgery. The design of new thermoelectric devices is also described, which provide active cooling/heating of irrigation fluid or eye structures, and which create opportunities for controlling thermal intraocular processes both intraoperatively and in the pre- and postoperative periods.